Legal codes and talking trees : indigenous women's sovereignty in the Sonoran and Puget Sound Borderlands, 1854-1946 /: indigenous women's sovereignty in the Sonoran and Puget Sound Borderlands, 1854-1946. ([2016]) - Jagodinsky, Katrina
No abstract available